Flipping the STEM Classroom: Pilot Study Findings - Brown, Mark A.; Edwards, Melissa; Alshiraihi, Ilham; Bowser, Gillian (Social Science Learning Education Journal, 2016)
In the past decade, an increasing body of STEM education research has emphasized the need to address the diverse learning needs of science, technology, engineering, and mathematics (STEM) students in higher education. Yet, the majority of STEM classes throughout the world still rely upon a traditional lecture format that reaches only a subset of student learning styles. As a result, many students struggle to master the complex material in STEM courses which often leads to lower academic performance and/or higher rates of attrition.The Flipped Classroom Model in STEM education has been widely documented for its ability to better engage broad audiences of students with diverse learning needs.We have implemented this model in courses in molecular biology, ecology, introductory microbiology, field research methods, and biotechnology. Overall, student performance was significantly higher in courses in which our flipped classroom innovations were implemented. Herein, we present preliminary findings of our pilot flipped classroom studies.